2007
DOI: 10.2337/db06-0552
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Responses to Islet Antigens Improves Detection of Autoimmune Diabetes and Identifies Patients With More Severe β-Cell Lesions in Phenotypic Type 2 Diabetes

Abstract: Latent autoimmune diabetes in adults or type 1.5 diabetes is considered to be a T-cell-mediated autoimmune disease. However, identification of patients is based commonly on autoantibody (Ab) detection. To determine whether measuring T-cell reactivity to islet proteins compared with measuring Abs improves detection of autoimmune diabetes and how ␤-cell function correlates with T-cell reactivity compared with Ab positivity, we assessed the T-cell proliferative responses and Ab responses (islet cell autoantibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Relatives were typed for HLA class II DRB1, DQA1, and DQB1 alleles using DNA-based typing with oligonucleotide probes, as previously reported (30). C-peptide levels were measured by an immunoenzymometric assay using the Tosoh AIA-600II autoanalyzer (Tosoh Bioscience, South San Francisco, CA) (31). The glucose oxidase method was used to measure the plasma glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Relatives were typed for HLA class II DRB1, DQA1, and DQB1 alleles using DNA-based typing with oligonucleotide probes, as previously reported (30). C-peptide levels were measured by an immunoenzymometric assay using the Tosoh AIA-600II autoanalyzer (Tosoh Bioscience, South San Francisco, CA) (31). The glucose oxidase method was used to measure the plasma glucose.…”
Section: Methodsmentioning
confidence: 99%
“…*Measured only at the clinical laboratory. 1Genotyping at the HLA class II locus (IDDM1) was performed using the direct sequencing of separately amplified exons 2 of DRB1, DQA1, and DQB1.^Cellular immunoblotting was performed on blood mononuclear cells to test for the presence of islet-specific T cells, as described previously (5). Control subjects without diabetes respond to 0-3 blots, whereas patients with autoimmune diabetes respond to 4-18 blots (5).…”
mentioning
confidence: 99%
“…It was hypothesized that the higher sensitivity of T-cell responses could be due to the capacity of T-cells to react with unknown islet antigens (40). In that study, however, IA-2 immunoreactivity was evaluated with IA-2 IC (605-979) and not with IA-2 (256 -760) construct.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it was shown that the islet proteins recognized by T-cells and autoantibodies in type 1 diabetic and LADA patients may be in part different (39) and that measures of multiple islet protein T-cell responses in type 2 diabetic patients may improve the identification of patients with autoimmune diabetes compared with autoantibody assess- ment alone (40). It was hypothesized that the higher sensitivity of T-cell responses could be due to the capacity of T-cells to react with unknown islet antigens (40).…”
Section: Discussionmentioning
confidence: 99%